MANAGEMENT OUTCOME OF RESIDUAL COMMON BILE DUCT STONES AT AGA KHAN UNIVERSITY HOSPITAL - Khan, Muhammad Rizwan; Naureen, Sameera; Hussain, Dildar; Azami, Rizwan (Journal of Ayub Medical College Abbottabad, 2005)
Background: The frequency of residual common bile duct (CBD) stones in patients with previous cholecystectomy ranges from 2-10%, and a minimally invasive approach is generally recommended for these patients. This study reviews the experience in the management of residual CBD stones at the Aga Khan University Hospital. Methods: All adult patients diagnosed to have residual CBD stones, from 1993 to 2001, were identified and analyzed in terms of the treatment modality utilized and its associated complications. The role of endoscopic sphincterotomy was particularly analyzed in our set-up. Results: The study population consisted of 66 patients. The mean age was 52 (range:18-84 years) years with a female to male ratio of 51:15. The primary mode of management consisted of endoscopic sphincterotomy in 61 patients (92.5%). The initial clearance rate for these patients was 75%, while the remaining 25% required ancillary procedures to achieve a complete clearance. Procedure related complications were observed in 17 (28%) patients, with zero mortality. The other 5 patients (7.5%) underwent an open choledochotomy as a primary procedure with no further complications. Conclusions: Endoscopic sphincterotomy is the most frequent treatment modality used for the management of residual CBD stones at our hospital. Although initial success rate seems low, the fact that endoscopic sphincterotomy is a less invasive procedure justifies its preferential utilization. The study does not compare the results of endoscopic management with open surgery, as the number of patients managed by open choledochotomy is very small. Keywords: Common bile dust stones, Retained common bile duct stones, Endoscopic sphincterotomy, Endoscopic retrograde cholangiopancreaticography